Training Access, Reciprocity, and Expected Retirement Age - Raymond Montizaan; Andries de Grip; Didier Fouarge (Institute for the Study of Labor (IZA), 2015)
This paper investigates whether employers can induce employees to postpone retirement by offering access to training courses that maintain job proficiency. We use unique, matched employeremployee surveys for the Dutch public sector, which include detailed information on a wide range of HR practices applied in the organization, as well as the expected retirement age of its employees. We find that training policies, as reported by employers, are significantly positively related to employee expected retirement age, irrespective of whether employees actually participate in training. We show that this positive relationship is driven by employees' positive reciprocal inclinations, indicating that provision of training may serve as a tool to motivate older employees in their job and consequently to retire later. The provision of training access may therefore complement existing pension reforms in many industrialized countries that aim to increase labor-force participation of older workers. Robustness analyses indicate that the relationship between offering training access and expected age of retirement is unlikely to be driven by reverse causality, self-selection, or the presence of other organizational characteristics.
Keywords: J24; J31; I2; 330; training access; reciprocity and retirement